Disruptive behaviour in compulsory secondary education classrooms: a multi-informant analysis of the perceptions of teachers and students - Martínez Fernández, Mª Belén; Chacón Gómez, Jose Carlos; Díaz-Aguado Jalón, María José; Martín Babarro, Javier; Martínez Arias, Rosario (Pulso. Revista de educación, 2020)
This study explores the relationship between disruption and three sets of indicators on school climate from a multi-informant approach. The data came from 4055 teachers and 16017 students from 187 secondary schools. The three dependent variables were teachers’ and students’ perceptions of disruption, and students’ admitting having participated in disruptive actions. The indicators chosen as predictors included a first group related to the school-climate quality, a second one about organizational measures that could improve this climate, and a third group about obstacles that deteriorate it. The results showed that teachers’ perceptions have a higher relation with the three sets of predictors. Meanwhile, indicators of obstacles to coexistence were those who showed greater variance associated with the three measures of disruption. It was found that, when teachers feel valued and respected by families, this is associated to lower levels of teachers’ perceived disruption and students’ admitted disruption. The analysis of the obstacles in achieving a good school climate shows that disruptive and aggressive behaviors are closely linked. Relations with teachers’ coercive behavior support the existence of growing disruption-coercion-disruption loops.
Keywords: Teacher-student perceptions; Disruptive behaviour; Secondary education; School climate; Multi-informant study